THE EFFECT OF COOPERATIVE LEARNING MODEL USING GAME-BASED MEDIA TOWARD STUDENTS’ LEARNING OUTCOMES AND ACTIVITY - Rahma, Yulia; Djulia, Ely (JURNAL PENA SAINS, 2024)
This study aims to determine the effect of the implementation of the Team Games Tournament (TGT) type cooperative learning model assisted by wordwall quiz media on earth and solar system material on learning outcomes and activeness of seventh grade students of SMPN 6 Kisaran. The study used a Quasi Experimental design with a Pretest and Posttest Control Group Design research design. The sample consists of two classes, namely the experimental class with the TGT learning model and the control class using the direct learning model with a total of 32 students each. Sampling was done by random sampling technique. Data collection was carried out using tests and observations. The data were analyzed by testing the hypothesis using the Mann Whitney test on student learning activeness and the Independent Sample T-test on student learning outcomes. The results of observations of student learning activeness show that the average value of student learning activeness of the experimental class is 79.2 which is included in the category of very active and the control class is 65.2 which is included in the active category. The pretest learning outcomes of students in the experimental class showed an average value of 36.6 students and in the control class 33.6. The posttest learning outcomes of students in the experimental class showed an average score of 78.4 with 24 students complete and in the control class 57.3 with 4 students complete. Hypothesis testing shows that there are significant differences in student activeness and learning outcomes in the experimental class using the Teams Games Tournament Type Cooperative learning model assisted by Wordwall Quiz compared to the control class using the direct learning model on solar system material.